Immature Platelet Fraction Examination in Assessing Thrombotic Risk in Patients with Diabetes Mellitus with Vascular Disorders - Sari, Atika Indah (Eduvest - Journal of Universal Studies, 2025)
Diabetes mellitus (DM) is a chronic metabolic disorder associated with an elevated risk of vascular complications due to enhanced platelet activation and hypercoagulability. Immature Platelet Fraction (IPF), a parameter measurable via automated hematology analyzers, has been proposed as a potential biomarker for thrombotic risk in DM patients. However, the utility of IPF in this context remains controversial due to inconsistent findings. This study aims to evaluate the clinical relevance of IPF in predicting vascular disorders in DM patients through a systematic review of existing literature, focusing on identifying its diagnostic accuracy and proposing directions for further research. Using a literature review approach, the study analyzed secondary data from peer-reviewed journals and clinical studies published between 2012 and 2025. A total of 14 key references were selected based on their relevance and methodological rigor. Data were thematically analyzed and interpreted using citation management tools. The results indicate that IPF levels tend to be elevated in DM patients with vascular complications, reflecting increased platelet turnover and activity. However, inconsistencies remain regarding its predictive validity, as some studies report significant correlations while others do not. Reference values for IPF also vary by population and instrument. This study suggests that although IPF holds promise as a thrombotic risk marker in DM, further empirical research is essential to establish standardized reference values and evaluate its integration with other biomarkers in clinical practice.